Implementasi Pendidikan Karakter Dalam Perkembangan Sosial Emosional Anak TK - rahayu, sri; Nasaruddin, Nasaruddin; Fitri, Riskal (ALENA : Journal of Elementary Education, 2024)
The implementation of character education in the social-emotional development of early childhood includes the values ??of discipline, independence, and social awareness and tolerance. The aim of this research is to determine the reality of character education in social-emotional development, the implementation of character education in children's social-emotional development at the Aisyiyah Bustanul Athfal Baji Pa'mai Kindergarten, Maros Regency. This research is qualitative research with descriptive research type. Teachers and students were involved as main informants. Data collection techniques used include interviews, observation and documentation. Data analysis by collecting data, reducing data, presenting data, verifying data and drawing conclusions. The research results show the reality of character education in social emotional development: Character education in PAUD helps shape children's personality and morals from an early age. Children who receive character education tend to have better social skills. Implementation of Character Education in Children's Social Emotional Development: Learning is carried out every day through activities inside and outside the classroom. The majority of students are in the stage of starting to develop and develop according to expectations from indicators of self-awareness, a sense of responsibility for themselves and others as well as prosocial behavior.